Pressure Measurements, Lesion Distribution and Outcome in Peripheral Artery Disease - Wickström, Jan-Erik (fi=Turun yliopisto|en=University of Turku|, 2023)
Peripheral artery disease (PAD) causes increased all-cause and cardiovascular (CV) mortality. These increases have been associated with abnormal ankle-brachial indices and the extent of atherosclerotic lesions as measured by radiological imaging. Reported associations of outcome in regard to systolic toe pressure (TP) are scarce, and those associations in regard to lesion distribution have been ambiguous. This thesis has two aims. First, to clarify the relationship of TP with outcome in patients with symptomatic PAD. Second, to clarify the association of anatomical distribution and extensiveness of angiographically detected lower extremity atherosclerotic lesions with outcome in the same patients. This thesis retrospectively reviews 887 patients whom underwent digital subtraction angiography (DSA) for the following: peripheral pressure measurements, DSA images and causes of death. Within a median 4.6 years followup, almost half of the patients had died, and of these deaths 60% had been due to CV causes. Angiographic lesion distribution, severity and TP were independently associated with increased all-cause and CV mortality. A predominantly or exclusively crural distribution of atherosclerotic lesions in the lower extremities and widespread lesions in the crural arteries predicted increased CV and all-cause mortality in symptomatic PAD patients undergoing DSA. Estimated cumulative survival and freedom from CV death could be stratified according to TP categories < 30 mmHg, 30–49 mmHg and ≥ 50 mmHg in the affected lower extremity. TP < 30 mmHg was independently associated with increased all-cause and CV mortality and decreased amputation-free survival. Bilaterally low TP was associated with a particularly poor outcome.

Alaraajojen tukkiva valtimotauti johtaa lisääntyneeseen kokonais- ja kardiovaskulaarikuolleisuuteen. Poikkeavan nilkka-olkavarsipaineindeksin ja kuvantamistutkimuksissa määritetyn tautimuutosten laajuuden on osoitettu liittyvän tähän. Lopputuleman yhteyksiä systoliseen varvaspaineeseen on raportoitu niukalti ja sen raportoidut yhteydet tautimuutosten sijainnin jakautumiseen ovat ristiriitaisia. Tämän väitöskirjan tarkoitus on selventää varvaspaineen ja angiografisten tautimuutosten anatomisen jakauman sekä laajuuden yhteyttä oireista perifeeristä valtimokovettumatautia sairastavien potilaiden ennusteeseen. Väitöskirjassa tarkasteltiin retrospektiivisesti perifeerisiä valtimopainemittauksia, varjoainekuvia ja kuolinsyitä 887:lla oireisella alaraajojen tukkivaa valtimotautia sairastavalla potilaalla, joille tehtiin alaraajojen varjoainekuvaus. Keskimäärin 4,6 vuoden seurannan aikana lähes puolet potilaista kuoli, joista 60 % kardiovaskulaarisista syistä johtuen. Angiografisten tautimuutosten sijainnin jakautuminen ja vaikeusaste, sekä varvaspaine assosioituivat itsenäisesti lisääntyneeseen kokonaisja kardiovaskulaarikuolleisuuteen. Valtaosin tai yksinomaan säären tasoon paikantuvat valtimotautimuutokset ja laaja-alainen säärivaltimoiden tauti ennustivat lisääntynyttä kardiovaskulaari- ja kokonaiskuolleisuutta oireista alaraajojen valtimokovettumatautia sairastavilla potilailla, joille tehtiin alaraajojen varjoainekuvaus. Kumulatiivinen elossaolo ja kardiovaskulaarikuolemalta välttyminen voitiin ryhmittää oireisen alaraajan varvaspaineluokkien < 30 mmHg, 30–49 mmHg ja ≥ 50 mmHg perusteella. Varvaspaine < 30 mmHg oli itsenäinen riskitekijä lisääntyneelle kokonais- ja kardiovaskulaarikuolleisuudelle. Molemminpuolisesti alhaisiin varvaspaineisiin liittyi erityisen huono ennuste.